Prevalence and factors associated with the development of mental health disorders among pregnant mothers - Mohd Arifin, Siti Roshaidai; Ismail, Anis Sabirah; Samsudin, Suhaiza; Hassan, Noor Artika; Wan Mamat, Wan Hasliza (2019)
Introduction: About 10% of pregnant women have mental health problems during pregnancy worldwide. Although previous studies had concentrated on the psychological health of postnatal women, prevalence and factors contributing to antenatal mental disorders remain unclear. Objectives: The aim of this study was to determine prevalence and factors associated with antenatal anxiety, worry, and depression among pregnant women. A total of 262 women who attended antenatal visit at four Mother and Child Health clinics in Pahang had participated in this cross-sectional study. The social support, anxiety, worry, and depressive symptoms were measured using the Multidimensional Scale of Perceived Social Support (MSPSS), State Trait Inventory (STAI), Cambridge Worry Scale (CWS), and the Edinburgh Postnatal Depression Scale (EPDS) respectively. Results: Of these women, 22.5% had anxiety, 79% had worry, and 20.2% had depressive symptoms within their pregnancy period. Women with lower education background, primiparous women, and working women are at risk of experiencing worry in pregnancy. This study has proven that social support plays a significant role in alleviating worry during pregnancy. Conclusion: Considering that the high level of worry in pregnancy could result in negative pregnancy outcomes and postnatal depression, there should be a screening tools used to measure psychological wellbeing of the pregnant mother within the clinical practice. The element of social support should be included in the intervention targeting women with lower educational level, primiparous and working mothers.